New trends in the recreational industry - G. G. Mikhailov; V. V. Pashkov; T. N. Lavrova (Современная наука и инновации, 2024)
In this article, we have considered the current trends in the development of the tourism and recreation industry under international restrictions. The recreational industry is an important sector of the economy, contributing to the development of regions with suitable conditions for organizing recreational activities. The authors of the article emphasize that for sustainable growth and improvement of the quality of services provided, it is important to consider and implement new trends that are observed in the recreational industry. We have analyzed the impact of modern technologies, changes in consumer preferences and environmental factors on the development of this industry. We will also look at the prospects and challenges faced by enterprises in the recreational industry in the context of rapidly changing opportunities for international tourism and a shift in focus to domestic tourism. In addition, the article draws attention to the changing consumer preferences regarding recreational destinations for recreation.